Mental health of children with and without special healthcare needs and of their caregivers during COVID-19: a cross-sectional study. Issue 1 (30th June 2022) - Geweniger, Anne; Haddad, Anneke; Barth, Michael; Högl, Henriette; Mund, Annette; Insan, Shrabon; Langer, Thorsten
Abstract : Objective: To describe mental health outcomes and measures of pandemic burden of children with and without special healthcare needs, and their caregivers following the second wave of the COVID-19 pandemic in Germany. Design: This is the second of a sequential series of cross-sectional online surveys conducted among caregivers of children ≤18 years since the onset of the COVID-19 pandemic, administrated between 2 April 2021 and 31 July 2021. Main outcome measures: Child and parental mental health were assessed using the Strengths and Difficulties Questionnaire and WHO-5 Well-being index. Children with Special Healthcare Needs (CSHCN) were identified using the CSHCN-Screener. Descriptive statistics, linear and hierarchical logistic regression modelling assessed associations between parent-reported child mental health problems and measures of pandemic burden, disease complexity, caregiver mental well-being and socioeconomic status. Results: 521 participants were included in the final sample. There was a high prevalence of parent-reported mental health problems in n=302 (66.7%) children, particularly in CSHCN. Among caregivers, n=372 (72.5%) screened positive for depression. Logistic regression modelling showed a strong association of child mental health problems and disease complexity, parental mental well-being, increase in family conflict and inadequate social support. Conclusions: Our study identifies CSHCN as a particularly vulnerable group in terms of mental health outcomes. Psychosocial factors were important predictors of parent-reported child mental health problems. Policy measures should consider the importance of social support systems for vulnerable children and their families, and aim to provide accessible mental health support for caregivers.